ABDOMINAL SACROCOLPOPEXY VS VAGINAL SACROSPINOUS LIGAMENT FIXATION FOR VAGINAL VAULT PROLAPSES: Sequential Repair of Bilateral Ingniolasty - Choudhry, Abeera; Shukr, Irfan; Choudhry, Humaira; Bangash, Naila; Jan, Shahida (Pakistan Armed Forces Medical Journal, 2009)
Objective: To compare the success rate and outcome of two operations for vaginal vault prolepses-Vaginal Sacrospinous Ligament Fixation (SSL) versus Abdominal Sacrocolpopexy (SCP). Study Design: Prospective randomized controlled trial. Place and Duration of Study: Department of Obstetrics and Gynaecology CMH Peshawar between Jan 99 to Sep 2003 and Department of Obstetrics and Gynaecology MH Rawalpindi between Sep 2003 to Feb 2008. Patients and Methods: Thirty Women were randomly allocated to either procedure. There were a total of 15 patients in either arm. Follow up was at 3 and 6 months. Results: Thirty women with vault prolapse were selected and out of these, 15 each were randomized to SSL and SCL. The mean age of women was 54 years (range 42 – 70), mean weight 68 Kg (range 50 – 95 Kg), the duration of surgery was longer for SCP (46.1 versus 75.3 min, (p<0.001) versus SSL. Average blood loss was also more for SCP versus SSL (320.2 versus 407 ml (p<0.001). Post Operative hospital stay was less for SSL (3.4 days) versus SCP (6.1 days) (p<0.001). Regarding symptoms of persistent prolapse at 3 and 6 months only one patient had symptoms in sacrocolpopexy arm due to cystocoele. There was no evidence of recurrent vault prolapse. Objective assessment of prolapse was superior for abdominal surgery, but patient satisfaction was equal. Anatomical result of abdominal procedure seemed superior with vault mean vaginal length (5.09 versus 6.8cm (p<0.001), but sexual function was preserved equally in both arms. Conclusion: SSL is a patient friendly operation with shorter operation time and hospital stay. The anatomical results of SCP seem superior whereas functional results were equal in both arms.